2015
DOI: 10.1159/000369707
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Cancer Effect of Metabotropic Glutamate Receptor 1 Inhibition in Human Glioma U87 Cells: Involvement of PI3K/Akt/mTOR Pathway

Abstract: Background: Metabotropic glutamate receptors (mGluRs) are G-protein-coupled receptors that mediate neuronal excitability and synaptic plasticity in the central nervous system, and emerging evidence suggests a role of mGluRs in the biology of cancer. Previous studies showed that mGluR1 was a potential therapeutic target for the treatment of breast cancer and melanoma, but its role in human glioma has not been determined. Methods: In the present study, we investigated the effects of mGluR1 inhibition in human gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
2
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 55 publications
2
63
2
5
Order By: Relevance
“…Also, mTOR by L-Leucine reversed Schisandrin B's anti-cell metastasis action, and significantly increased number of cell migrated and invasive cell. Our finding suggested the involvement of PI3K/Akt/ mTOR cascade was in Schisandrin B's anti-metastasis and were consistent with previous researches that pointed out that resultant deregulation of the Akt/mammalian target of mTOR signaling pathway from these alterations has shown to be an important determinant of gliomagenesis [17,22].…”
Section: Discussionsupporting
confidence: 92%
“…Also, mTOR by L-Leucine reversed Schisandrin B's anti-cell metastasis action, and significantly increased number of cell migrated and invasive cell. Our finding suggested the involvement of PI3K/Akt/ mTOR cascade was in Schisandrin B's anti-metastasis and were consistent with previous researches that pointed out that resultant deregulation of the Akt/mammalian target of mTOR signaling pathway from these alterations has shown to be an important determinant of gliomagenesis [17,22].…”
Section: Discussionsupporting
confidence: 92%
“…As is well recognized, the key role of mTOR is as a repressor of autophagy; the decrease in mTOR activity can effectively initiate the autophagic response in glioma cells [34-36]. Activation of AMPK leads to the inhibition of mTOR, which also propels autophagy [33].…”
Section: Discussionmentioning
confidence: 99%
“…The activation of the MAPK pathway by different stimuli may lead to GSK3β inhibition [58,59,63]. In addition, as the major target of the PI3K, Akt regulates many downstream targets for the execution of its cell functions (such as cell growth and migration) [64][65][66]. Previous studies showed that Akt activation led to GSK3β phosphorylation [67,68], while others showed that lithium was able to activate PI3K and Akt and in turn to induce GSK3β phosphorylation and inactivation [69,70].…”
Section: Discussionmentioning
confidence: 99%